Efficient Access to Peptidyl‐RNA Conjugates for Picomolar Inhibition of Non‐ribosomal FemXWv Aminoacyl Transferase. Issue 4 (29th November 2012) - Fonvielle , Matthieu; Mellal , Dénia; Patin, Delphine; Lecerf, Maxime; Blanot, Didier; Bouhss, Ahmed; Santarem, Marco; Mengin‐Lecreulx, Dominique; Sollogoub, Matthieu; Arthur, Michel; Ethève‐Quelquejeu, Mélanie
Abstract Peptidyl–RNA conjugates have various applications in studying the ribosome and enzymes participating in tRNA‐dependent pathways such as Fem transferases in peptidoglycan synthesis. Herein a convergent synthesis of peptidyl–RNAs based on Huisgen–Sharpless cycloaddition for the final ligation step is developed. Azides and alkynes are introduced into tRNA and UDP‐MurNAc‐pentapeptide, respectively. Synthesis of 2′‐azido RNA helix starts from 2′‐azido‐2′‐deoxyadenosine that is coupled to deoxycytidine by phosphoramidite chemistry. The resulting dinucleotide is deprotected and ligated to a 22‐nt RNA helix mimicking the acceptor arm of Ala‐tRNAAla by T4 RNA ligase. For alkyne UDP‐MurNAc‐pentapeptide, meso‐cystine is enzymatically incorporated into the peptidoglycan precursor and reduced, and L‐Cys is converted to dehydroalanine with O‐(mesitylenesulfonyl)hydroxylamine. Reaction of but‐3‐yne‐1‐thiol with dehydroalanine affords the alkyne‐containing UDP‐MurNAc‐pentapeptide. The CuI‐catalyzed azide alkyne cycloaddition reaction in the presence of tris[(1‐hydroxypropyl‐1H‐1, 2, 3‐triazol‐4‐yl)methyl]amine provided the peptidyl‐RNA conjugate, which was tested as an inhibitor of non‐ribosomal FemXWv aminoacyl transferase. The bi‐substrate analogue was found to inhibit FemXWv with an IC50 of (89±9) pM, as both moieties of the peptidyl–RNA conjugate contribute to high‐affinity binding.